2007
DOI: 10.1121/1.2739806
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility experiments on measuring acoustical properties of rigid-frame porous media (round-robin tests)

Abstract: This paper reports the results of reproducibility experiments on the interlaboratory characterization of the acoustical properties of three types of consolidated porous media: granulated porous rubber, reticulated foam, and fiberglass. The measurements are conducted in several independent laboratories in Europe and North America. The studied acoustical characteristics are the surface complex acoustic impedance at normal incidence and plane wave absorption coefficient which are determined using the standard imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…Determining Young's Modulus Once Poisson's modulus has been calculated, Young's modulus is directly determined by (24).…”
Section: Polynomial Ratios Simulations Of Static Finite Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining Young's Modulus Once Poisson's modulus has been calculated, Young's modulus is directly determined by (24).…”
Section: Polynomial Ratios Simulations Of Static Finite Elementsmentioning
confidence: 99%
“…Pilon et al [43] defined a new parameter named as Frame Acoustical Excitability and established a critical value below which the theoretical absorption could be efficiently measured using a standing wave tube. Recently Horoshenkov et al [24] have carried out reproducibility experiments on the interlaboratory characterization of the acoustical properties of three types of consolidated porous media. As main conclusions, they state that:…”
Section: Introductionmentioning
confidence: 99%
“…16 where c 0 is the sound speed in fluid. The reproducibility of this method is discussed in ref., 12 where it was shown that the variation in the measured acoustical properties can be considerable if the material is not homogeneous. In the case of materials with high flow resistivity, the accuracy of this method is also dependent on the quality of the sample preparation and on the presence of the circumferential gap between the material sample and the wall of the impedance tube as shown in references.…”
Section: Methods For Parameter Inversion Based On Asymptotic Behaviourmentioning
confidence: 99%
“…There are two well-known methods of laboratory measurement of absorption, which have been described as international standards (ISO 105034, 1996;ISO 10534, 1998;ISO 354, 2003) in providing important databases regarding test materials, i.e., the reverberation room, and the tube method. A number of studies (Kosten, 1960;Makita et al, 1968a;Makita et al, 1968b;Cummings, 1991;Iwase and Izumi, 1995;Horoshenkov et al, 2007) have been conducted in order to check the effectiveness of the standard. Nevertheless, there are still issues that remain unresolved, e.g., the difficulty of measurements in situ because similar mounting conditions are difficult to reproduce.…”
Section: Introductionmentioning
confidence: 99%